Vulnerabilidade dos participantes de pesquisa: significados das relações entre participantes e pesquisadores - Oliveira, Luciana Alves de (2018)
The vulnerability on researches involving human being includes the reduction or impairment of individual’s self-determination ability. Several circumstances may determine the vulnerability situation. International regulations and consensus around ethics research are not enough to ensure respect for research participants and to prevent any harms arising from research. Research in hospitals has peculiarities about the health-disease process. This research sough to identify the research patient-participant situations of vulnerability occurring concomitantly with their treatment in a hospital in Goiânia-GO; and to analyze the meanings of vulnerability attributed by the actors involved in the context of research development in a hospital in Goiânia-GO. This was a qualitative approach of an ethnomethodology research based on Foucault's theoretical framework. Semi-structured interviews were conducted with 15 patients and 15 health professionals at a public hospital in Goiânia-GO. Three categories emerged from the interviews: "Changed lives", "Professional training" and "The ideal place". The results evidenced the tendency of the participants to understand the research as something positive that will bring important contributions for treatment, allowing the hope of the cure. The participants recognized the hospital as the ideal place to seek healing. However there were situations of weaknesses, such as the health care system itself and the communication between health professionals and patients. This suggests that the power existing in these relations still reiterates the maintenance of hierarchy and fragilities, affecting the exercise of autonomy by the patient. Thus, the speeches expressed and showed how power is established in that place, as well as the communication itself. Even not all participants perceived the weaknesses present in the research field, which amplifies the dimensions of the vulnerabilities. It is possible to conclude that the senses of vulnerability in this context cover the changes in the lives of those patients-participants, the process of training of the professionals and, also, the experience of the routines in that hospital considered reference for the treatment.